A comparison of 129S2/SvHsd and C57BL/6JOlaHsd mice on a test battery assessing sensorimotor, affective and cognitive behaviours: implications for the study of genetically modified mice. - Contet, C; Rawlins, J; Deacon, R (2001)
Mice from the 129S2/SvHsd (129) and C57BL/6JOlaHsd (C57) strains were assessed for performance on a test battery including sensorimotor, affective and cognitive measures, using established as well as modified paradigms. Marked strain differences were observed in measures of locomotion, motor coordination and anxiety: the 129 mice were typically less active and more anxious. In contrast, the strains did not markedly differ in muscular strength, habituation to an open field or spatial working memory. The data provide baseline parameters of behaviour against which genetically modified lines derived from these particular parental strains can be assessed.